Polymorphism specific Allele Frequencies on Cervical Cancer - Salih Saihood, Anwar; Jabbar Hussein , Khawlah; Sharif , Yasamin Hamza (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To evaluate the correlation of allele frequencies of IL-6 polymorphisms between healthy women and cervical cancer patients.Methods: The study involved gynecologists diagnosing abnormal cervical tissue in 100 women aged 17-60. Each woman provided two tissue samples: one for pap smear analysis and one for genetic research, along with a blood sample for IL-6 polymorphism analysis. Traditional polymerase chain reaction (PCR) was used for genetic analysis to confirm diagnoses. Allele-specific PCR (AS-PCR) was utilized to identify allelic polymorphisms. Pap smears identified cervical intraepithelial neoplasia (CIN) II and III, characterized by dysplastic cells and mitotic figures.Results: The diagnostic PCR data demonstrated that 36% of participants were HPV-infected, with the greatest infection rates (50%). The AS-PCR reported that the IL-6 (rs1800795) gene detected at 174 G/C position was presented with GG, GC, and CC genotypes. Conclusion: The result showed a significant alteration in the IL-6 (rs1800795) gene, strongly correlating with cervical cancer based on human papillomavirus infection.Keywords: cervix cancer, human papillomavirus, interleukin-6 polymorphism, genetic analysis.